Treatment patterns and clinical outcomes in stage III non-small-cell lung cancer: a long-term institutional experience in Switzerland (Swiss Medical Weekly, 2025)
STUDY AIM: Treatment of stage III non-small-cell lung cancer (NSCLC) has evolved rapidly in recent years. To improve our understanding of real-world outcomes in Switzerland, we report on our institutional experience at an academic lung cancer centre and describe treatment patterns and clinical outcomes over a multi-year period.METHODS: Patients diagnosed with stage III NSCLC between 2013 and 2023 were included in an ethics-approved institutional database. Based on tumour board decisions, the initial treatment strategy was defined for each patient. Overall and progression-free survival were calculated using the Kaplan-Meier method. A multivariate Cox regression analysis was performed to study the impact of different factors on clinical outcomes.RESULTS: A total of 315 patients with stage III NSCLC were included. Patients were a median of 68 years old, and two-thirds were male. The most common stage at diagnosis was IIIA (56%), followed by stage IIIB (36%) and IIIC (8%). A curative treatment approach was pursued in 88% of patients, and over 90% of these received definitive local treatment (surgery and/or radiotherapy). Rates of 1-year overall and progression-free survival improved from 64% and 47%, respectively, in 2013–2016, to 82% and 70% in 2020–2023. However, 49% of patients developed locoregional and/or distant recurrence. Results of the multivariate analysis are presented in the manuscript.CONCLUSIONS: Almost 90% of patients with stage III NSCLC underwent treatment with curative intent, with rates of treatment adherence that compared favourably to the literature. Although survival outcomes appear to have improved in recent years, the rates of disease recurrence remain high, reflecting a need for further improvements.